Students’Learning Experiences in Conceptualizing Differentiation in Secondary Level Mathematics Education - Roka, Jasbir; Khadka, Dambar Bahadur (Academic Journal of Mathematics Education, 2025)
Differentiation is a fundamental concept in calculus which is essential for multidimensional fields. Conceptualizing differentiation is an emerging issue in mathematics education globally. In this context, the study explores students’ learning experiences in conceptualizing differentiation at the secondary level of mathematics education in Birendranagar, Surkhet. Using a phenomenological inquiry within the interpretative research paradigm, data were collected through semi-structured interviews with six purposively selected public secondary-level students in Surkhet, Nepal and analyzed thematically to gain insight into learning practices and conceptual understanding. The findings reveal that students struggle with abstract ideas such as limits, continuity, and rate of change, as well as with connecting visualizations, and algebraic representations. This study also suggests a contextulized teaching approach to improve conceptual development and meaningful learning in differentiation. This study would provide practical implications for educators, policy makers, mathematics educators, students, and concerned stakeholders.